Development of Physics E-Module Based on Discovery Learning to Improve Students’ Scientific Literacy - Shofia Maghfiroh; Insih Wilujeng; Jumadi Jumadi; Dewi Masyitha (Jurnal Penelitian Pendidikan IPA, 2023)
The education system in the current era of globalization has changed due to the COVID-19 pandemic. Learning takes place in the new normal transition period using the blended learning method. Blended learning that emphasizes students to study offline and online can lead to a lack of student scientific literacy. This study developed an e-module of physics in health to facilitate student learning that can be used for offline and online learning. This study aims to describe e-modules based on discovery learning about hydrostatic pressure submaterial. This type in research by adapting 4-D development model (define, design, develop, desseminate). The research instrument used was the media questionnaire, student response sheets, and scientific literacy questions. The results showed that the priority of the experts was 94% very well. Student responses to the e-module obtained a value of 90% very good category. The N-Gain value was obtained at 0.4 in the medium category. Based on the results of this study, it can be said that the e-module based on the discovery learning is effective in improving students' scientific literacy skills.